A novel polyaspartic acid derivative with multifunctional groups for scale inhibition application. Issue 7 (3rd April 2018) - Zhang, Ying; Yin, Hongquan; Zhang, Qingshan; Li, Yunzheng; Yao, Pengjun; Huo, Hongyu
ABSTRACT: Polyaspartic acid is a green biodegradable antiscalant and widely applied in water treatment field. However, its scale inhibition efficiency is not prominent, especially for calcium orthophosphate. So we introduced acylamino and hydroxyl groups simultaneously to prepare a novel polyaspartic-acid derivative (PASPTU) with multifunctional groups by the reaction of polysuccinimide with threonine and urea. The graft copolymer was analyzed by using nuclear magnetic resonance, gel permeation chromatography, thermogravimetric analyzer and Fourier transform infrared spectroscopy. Its scale inhibition performance for calcium orthophosphate, calcium sulfate and calcium carbonate was evaluated. The findings showed that the scale inhibition rates of the graft copolymer reached up to 100% for calcium orthophosphate, 100% for calcium sulfate and 91% for calcium carbonate at certain dosages. The findings above showed that the copolymer had excellent scale inhibition efficiency for calcium salts in water treatment processes.